Word Variant Identification in Old French - Peter Willett (Information Research: An International Electronic Journal)
Increasing numbers of historical texts are available in machine-readable form, which retain the original spelling, which can be very different from the modern-day equivalents due to the natural evolution of a language, and because the concept of standardisation in spelling is comparatively modern. Among medieval vernacular writers, the same word could be spelled in different ways and the same author (or scribe) might even use several alternative spellings in the same passage. Thus, we do not know,a priori, how many variant forms of a particular word there are in such texts, let alone what these variants might be. Searching on the modern equivalent, or even the commonest historical variant, of a particular word may thus fail to retrieve an appreciable number of occurrences unless the searcher already has an extensive knowledge of the language of the documents. Moreover, even specialist scholars may be unaware of some idiosyncratic variants. Here, we consider the use of computer methods to retrieve variant historical spellings.